No pulsar da clínica: a repetição e as produções corporais de uma criança - Xavier, Francisca Lenira (2008)
This study investigates the Repetition of movements shown in a stereotypical case of a child three years old. In line with the psychoanalysis model of search, this work presents fragments of the clinic process, the locus for the observation of repetitive, ritualized and choreographically movements of this child who used not to speak. The contrast between their movements and the issuance of a word verbalized at the end of the treatment caused the following question: repetition in this child production would be a reproduction of the same or would be directing for the difference? In the psychiatric speech, the stereotypes are listed as diagnostic criteria for certain mental disorders. In the psychoanalysis studies a question about the psych nature of ritualistic gestures apparently without purpose or direction is included. Thus, the route followed was the reading of the theoretical concept of repetition in the psychoanalytic works of S. Freud and J. Lacan. With Freud, the repetition is linked to the transfer and resistance. In that context, when it appears in act, in the place of the talk, it constitutes a particular way of remembering. But the existence of a force in the psychic apparatus that acts independent and involuntarily of the Principle of pleasure (the repetition compulsion) subsidizes the discovery of Freudian pulsion of death that is the tendency to return to itself. In the Lacan reading, the function of Repetition is magnified, as it fulfils two functions: the automaton - reminders of repetitive signs, and that the service of tiqué - the meeting of the subject with his lack constituent. In this sense, repetition is not simply a reproduction, but the search for new, the difference, caused by the lack of continuity that pushes the circuit. Finally, the clinic process and the theoretical readings made the comprehension of the child repetitive and choreographically movements and the pronouncement of a "good-bye", full of meaning. This repetitive scenario which is full of questions, by this very nature, insists in remains inconclusive